Analysis of Clinic Compliance With Health Minister Regulation No.14 Of 2021 in Karawang District 2024 - Rifa Sofia Marwati; Fajar Saputra (Sean Institute, 2025)
Ministry of Health Regulation No. 14 of 2021 regulates the standards of facilities, health workers, and clinic operations to ensure the quality of health services. However, the level of clinic compliance with this regulation still varies, especially in terms of the completeness of infrastructure facilities and the number of health workers who meet the standards. Therefore, this study aims to analyze clinic compliance with these regulations in Karawang Regency in 2024. Methods This study used a qualitative approach with interview and observation methods. Interviews were conducted with three main informants consisting of clinic owners/managers, medical personnel, and Health Office officers, as well as two supporting informants from patients or service users. Observations were made to assess the suitability of facilities and the number of health workers with the provisions in Permenkes No. 14 of 2021. The results showed that most clinics have tried to comply with the regulation, especially in providing examination rooms and basic facilities. However, there are still some clinics that have not met the standards, especially in the provision of appropriate action rooms and an adequate number of health workers. The main factors affecting compliance include budget constraints, lack of medical personnel, and lack of understanding of the applicable regulations by clinic managers. Conclusion Increased supervision, socialization of regulations, and support from local governments in the form of budgets and incentives for medical personnel in clinics are needed to improve compliance with Permenkes No. 14 of 2021.